A Group Guidance Guide using the Six Thinking Hats Technique to Improve Problem-Solving Skills for Vocational High School Students in Preparation for Work Practice - Riska Handayani; Elisabeth Christiana; Bakhrudin All Habsy (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Problem-solving skills during industrial work practice are essential competencies that vocational high school (SMK) students must possess. This study aims to develop a group counseling guide using the Six Thinking Hats technique to enhance the problem-solving skills of students in technology and engineering vocational programs that meet acceptability criteria. The guide is designed for use by guidance and counseling teachers in preparing students for industrial internships. This research employed the ADDIE development model, which includes the phases of analysis, design, development, implementation, and evaluation. The preliminary study involved 362 vocational high school students who were undergoing industrial work practice. The main subjects of the study consisted of two expert validators from the state university and two user validators, namely guidance and counseling teachers. The research instruments included an acceptability questionnaire and a problem-solving skills questionnaire. Data were analyzed using descriptive analysis to assess the feasibility of the guide based on expert and user validation results, and the effectiveness was tested using the Wilcoxon Signed Ranks Test. The results indicated that the group counseling guide using the Six Thinking Hats technique met the acceptability criteria and was deemed appropriate for use by practitioners. This guide is expected to assist guidance and counseling teachers in developing more effective counseling strategies to prepare students for industrial work practice.